The neglected role of Faith-based Organizations in prevention and control of COVID-19 in Africa. (27th August 2020) - Vilakati, Phesheya Ndumiso; Villa, Simone; Alagna, Riccardo; Khumalo, Bongani; Tshuma, Sarah; Quaresima, Virginia; Nieman, Nicole Rose; Cirillo, Daniela Maria; Raviglione, Mario Carlo
Abstract: The COVID-19 pandemic has exposed health system weaknesses of economically wealthy countries with advanced technologies. COVID-19 is now moving fast across Africa where small outbreaks have been reported so far. There is a concern that with the winter transmission will grow rapidly. Despite efforts of African Governments to promptly establish mitigating measures, rural areas, especially in sub-Saharan Africa, risk being neglected. In those settings, faith-based and other non-governmental organizations, if properly equipped and supported, can play a crucial role in slowing the spread of COVID-19. We describe our experience in two rural health facilities in eSwatini and Ethiopia highlighting the struggle towards preparedness and the urgency of international support to help prevent a major public health disaster.